Pregnant Women in Sport Climbing – Is there a Higher Risk for Preterm Birth? - Drastig, Jan; Hillebrandt, David; Rath, Werner; Küpper, Thomas (Zeitschrift für Geburtshilfe und Neonatologie, 2017)
Sport climbing is a popular recreational sport with an increasing proportion of female athletes. International recommendations emphasize the physical and mental benefits of regular sport activity during any uncomplicated pregnancy. In this context, sport climbing is associated with a high risk potential.The aim of this study was to examine if there is a higher risk for preterm birth in active climbing athletes.Original manuscript.A retrospective self-report online survey in the German language collected data between September 2012 and November 2013. In addition to anthropometric and demographic data, data on climbing experience, preferred climbing discipline, skill level and changes of climbing habits during pregnancy, known risk factors for preterm birth and information on delivery and the newborn were requested. The rate of preterm birth of the survey was tested with Fisher’s exact test with information from the German Federal Statistical Office.Sample size was 32. 72% had a university degree, 81% were primiparous, all were singleton pregnancies. A 33rd questionnaire was excluded because of described preeclampsia. Age ranged between 21 and 39 years, climbing experience before pregnancy between 2 and 24 years, and skill level before pregnancy between 4 and 7 on the UIAA scale (International Climbing and Mountaineering Federation). Half of the women climbed until the 36th week and 90% adjusted their climbing habits mostly by reducing climbing difficulty and doing more top roping. 2 preterm births in the 36th week of gestation were found (2 from 15, p=0.36). According to the data from the German Federal Statistical Office, 8.9% births in the year 2013 in Germany were preterm.This is the first study investigating the risk of preterm birth in recreational sport climbing athletes. No significantly higher proportion of preterm birth could be found. Limitations are small sample size and high social status of participants. What is known about the subject: Sport climbing is not a high-risk sport, but it is regarded as a dynamic whole-body exercise and has been shown to be a valuable therapy for various physical and mental diseases. Higher performance levels are associated with overuse damage to the upper extremity, especially the fingers. What this study adds to existing knowledge: This is first study investigating climbing-related risk of preterm birth. When continuing sport climbing as a recreational activity during an uncomplicated pregnancy, experienced athletes do not have a higher risk of adverse events.
Keywords: pregnancy; preterm birth; sports climbing